Profile of diabetic patients accompanied by the pharmaceutical assistance of Piauí, Brazil - Rodrigues de Oliveira Castelo Branco, Renata; Barbosa Ferreira, Pablo Ricardo; Pereira, Sean Telles; Ferreira de Araújo, Éverton José; Mota Conceição, Amanda; de Sousa Reis, Flávia Mylla; Rezende Júnior, Luís Mário; Barbosa Ferreira, Pablo Ricardo (O Mundo da Saúde, 2018)
Diabetes mellitus consists of a chronic disease that currently stands out for its associated morbidity and mortality. The therapy is based on the association of different drugs and requires a change in the habits of the patients. The objective of the present study was to analyze the clinical and epidemiological profile of patients with type 2 diabetes mellitus assisted by the Specialized Component of Pharmaceutical Assistance of the state of Piauí. This was a descriptive, cross-sectional study and analysis of social, demographic, economic, biochemical and anthropometric parameters. From the 93 participants, 66.7% were female, 57% had an average age of 60.5 years and 50.5% had a weight above 69 kg. The predominant family income was one minimum wage salary and the level of education reported was completed secondary education. It was found that 53.8% of the participants practiced regular physical activity and 87.1% had food restrictions. The most commonly used drug was vildagliptin. It was proven that 52.7% had unsatisfactory glycemic control considering the levels of HbA1c, as well as a necessity of a public state clinical protocol that regulates the dispensation of oral hypoglycemic agents in the state.